2004
DOI: 10.1507/endocrj.51.165
|View full text |Cite
|
Sign up to set email alerts
|

Positive Relationship between Androgen and the Endocrine Disruptor, Bisphenol A, in Normal Women and Women with Ovarian Dysfunction

Abstract: Abstract. This study was performed to investigate the serum levels of bisphenol A (BPA), an endocrine disruptor, in women with ovarian dysfunction and obesity. Fasting serum samples were obtained from 19 non-obese and 7 obese women with normal menstrual cycles: 7 patients with hyperprolactinemia, 21 patients with hypothalamic amenorrhea, and 13 non-obese and 6 obese patients with polycystic ovary syndrome (PCOS). BPA was measured by an enzyme-linked immunosorbent assay. BPA was detected in all human sera. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
291
5
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(309 citation statements)
references
References 21 publications
9
291
5
4
Order By: Relevance
“…For six of the articles, body composition (BMI, WC and/or weight) was the primary outcome of interest (62)(63)(64)67,71,74) . Seven studies included only women (65,67,69,73,74,77,78) , nine of the studies were in general adult populations (62)(63)(64)66,67,70,71,75,76) , one study included men and women ≥60 years (72) and another included only 70-year-old men and women (79) .…”
Section: Resultsmentioning
confidence: 99%
“…For six of the articles, body composition (BMI, WC and/or weight) was the primary outcome of interest (62)(63)(64)67,71,74) . Seven studies included only women (65,67,69,73,74,77,78) , nine of the studies were in general adult populations (62)(63)(64)66,67,70,71,75,76) , one study included men and women ≥60 years (72) and another included only 70-year-old men and women (79) .…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies have measured BPA in blood and serum samples from healthy male and nonpregnant female adults (Dirtu et al 2008;Fung et al 2000;He et al 2009;Hiroi et al 2004;Ikezuki et al 2002;Inoue et al 2000Inoue et al , 2001Kaddar et al 2009;Kuroda et al 2003;Liu et al 2007;Sajiki et al 1999;Sugiura-Ogasawara et al 2005;Takeuchi and Tsutsumi 2002;Takeuchi et al 2004;Volkel et al 2005;Yang M et al 2009;Yoshimura et al 2002) (Table 3). Of these studies, five used ELISA, one used a radioimmunoassay (RIA), and the remainder used analytical chemistry to assess BPA concentrations.…”
Section: Internal Dosage Assessment From Blood Measures Of Bpamentioning
confidence: 99%
“…Two studies found women with polycystic ovarian syndrome (PCOS) had higher serum levels of BPA than did healthy control women (Takeuchi and Tsutsumi 2002;Takeuchi et al 2004). These studies also found a positive association between serum testosterone levels and BPA concentrations; this finding is especially interesting because it provides a potential basis for gender-biased exposures or metabolism of BPA (Takeuchi et al 2006).…”
Section: Healthymentioning
confidence: 99%
“…We reported that BPA was detectable not only in the serum but also in several biological fluids, including amniotic fluid, demonstrating human fetal exposure to BPA through the placenta [15]. It is interesting to note that there was a gender difference in serum BPA concentrations in humans [16] and, more recently, determination of serum BPA concentrations in women with or without ovarian dysfunction revealed that BPA levels may vary according to the endocrinological status of subjects [17]. BPA levels in patients with endometrial hyperplasia and endometrial cancer, both of which are estrogen-related uterine disorders, were lower compared to those in normal controls [18].…”
mentioning
confidence: 99%